The Application of Istisna' Contract in Islamic Micro Finance Institution (Case Study in Islamic Cooperative BMI) - Muhamad Komarudin; M. Rasyid Guntur Pratomo (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to explore the implementation of the Istishna contract in investment financing at Islamic Cooperative BMI. The study addresses the issue that, fundamentally, the Istishna contract is a sales contract, not an investment contract. As a result, an in-depth analysis is needed to assess the permissibility of using Istishna in investment financing or to consider potential adjustments in the financing model or contract type. The research uses a qualitative descriptive approach, gathering data through interviews and secondary sources such as the cooperative’s website, reports, and guidelines. It examines how Istishna is applied in investment financing and its adherence to Sharia principles, aiming to determine its suitability for use in such financing at Islamic Cooperative BMI. The findings indicate that the Istishna contract used in investment financing at Islamic Cooperative BMI aligns more closely with DSN MUI Fatwa No. 06/DSN MUI/IV/2000 on Istishna, which involves a straightforward contract between two parties. This differs from DSN MUI Fatwa No. 32/DSN-MUI/IX/2002 on Sharia bonds, where Istishna is applied in investment schemes, and also does not align with DSN MUI Fatwa No. 22/DSN MUI/III/2002 on parallel Istishna, as the cooperative already has a company dealing in building materials. Although the Istishna-based financing at Islamic Cooperative BMI complies with DSN MUI Fatwa No. 06/DSN MUI/IV/2000, it is suggested that the cooperative adopt terms such as consumptive financing, productive financing, property ownership financing, or other appropriate terms for financing schemes involving Istishna contracts. This is because cooperative members act as buyers seeking financing for development projects like housing, sanitation, and clean water provision, rather than functioning as investors.